Effects of phlorotannin and polysaccharide fractions of brown seaweed Silvetia compressa on human gut microbiota composition using an in vitro colonic model - Vázquez Rodríguez, Benjamín; Santos Zea, Liliana; Heredia Olea, Erick; Acevedo Pacheco, Laura; Santacruz, Arlette; Gutiérrez Uribe, Janet A.; Cruz Suárez, Lucía Elizabeth (2021)
Few studies had demonstrated the interaction of phlorotannins and polysaccharides from algae on microbial diversity and growth of probiotic bacteria on the early stages of colonic fermentation. Silvetia compresssa hydroethanolic extract rich in phlorotannins and its isolated polysaccharides fraction enabled the proliferation of Bifidobacterium and Lactobacillus and increased total short-chain fatty acids synthesis compared to a negative control. Eckstolonol, dieckol and acacetin derivative in hydroethanolic extract were depleted after eight hours of in vitro colonic fermentation. After a 48 h fermentation, hydroethanolic extract showed high levels of acetic (104.82 µmol g− 1 wet feces) and propionic acids (78.58 µmol g− 1 wet feces), as well as an increase in Bifidobacterium (log10 6.77 CFU g− 1 wet feces) and Lactobacillus (log10 4.25 CFU g− 1 wet feces) growth. These results showed no significant difference with inulin (p > 0.05), suggesting the potential of Silvetia compresssa hydroethanolic extract to improve human gut microbiota.